Analgesic efficacy of oral tramadol–dipyrone combination in cats undergoing ovariohysterectomy - Fantoni, Denise Tabacchi; Yazbek, Karina Velloso Braga; de Lima, Isabela Torquato; Cavaco, Jéssica Sperandio; Brito, Amanda Cologneze; Barreto, Érica Vilela; Matera, Julia Maria; Ambrósio, Aline Magalhaes; Pereira, Marco Aurélio Amador (Frontiers in Veterinary Science, 2026)
IntroductionSelecting an appropriate analgesic for cats can be challenging due to potential unwanted side effects, short duration of action, or unsuitable presentation for home administration. This study aimed to evaluate the analgesic efficacy and safety of a fixed-dose oral combination of dipyrone and tramadol (Sindolor Cats® tablets) for postoperative pain control in cats undergoing ovariohysterectomy.MethodsThirty-six healthy female cats were randomly assigned to three groups (n = 12): GTD (dipyrone 12.5 mg/kg + tramadol 2 mg/kg), GT (tramadol 2 mg/kg), and GD (dipyrone 12.5 mg/kg). Treatments were administered orally every 12 h for 5 days. Anesthesia was induced with propofol and maintained with isoflurane; all cats also received sacrococcygeal epidural lidocaine under ultrasound guidance. Pain was assessed using the CMPS-Feline and the Feline Grimace Scale (FGS). Physiological parameters (heart rate, respiratory rate) and serum cortisol were measured at baseline and at 2, 4, 6, and 24 h postoperatively. Rescue analgesia with morphine was administered when pain scores exceeded threshold values.ResultsThe GTD group required less rescue analgesia (1/12) compared to GT (4/12) and GD (5/12). Although not statistically significant, pain scores were consistently lower in GTD. Cortisol concentrations were significantly reduced in GTD at 4 h compared to GT and GD. Side effects such as sialorrhea were markedly lower in GTD (2/12) versus GT (9/12) and GD (12/12). No signs of cardiovascular or respiratory depression were observed in any group.DiscussionThe combination of dipyrone and tramadol in a single oral formulation provided superior analgesia and fewer adverse effects than either drug alone. Cats in the combination group required less rescue medication, had significantly lower cortisol values, and experienced fewer side effects.